Three‐dimensional analysis of seminiferous tubules and spermatogenesis in the musk shrew, Suncus murinus - Nakata, Hiroki; Yamaguchi, Mahiro; Omotehara, Takuya; Ichimura, Koichiro; Yi, Shuang‐Qin; Iseki, Shoichi (Journal of anatomy, 2025)
We reconstructed in three dimensions all seminiferous tubules in the testes of 1‐ and 8‐week‐old musk shrews (Suncus murinus), a small experimental mammal belonging to the family Soricidae, order Eulipotyphla that preserves the primitive characteristics of mammalian species. Quantitative analyses revealed that the basic structure of seminiferous tubules at 1 week postpartum remained consistent into adulthood. A single dominant seminiferous tubule with extensive branching accounted for more than 90% of the length of all tubules, a feature distinct from that in mice and rats. Pachytene spermatocytes were observed in the seminiferous epithelia of most tubules at 1 week, which was markedly earlier than in mice and rats. At 8 weeks, a mosaic pattern of active and inactive areas of spermatogenesis was observed through the length of seminiferous tubules, a feature distinct from that in mice and rats. The percentage of active areas was significantly lower in tubule portions near the rete testis. The unique characteristics of seminiferous tubules in the musk shrew will provide a basis for investigating not only the phylogeny of testis functions but also the regulation of spermatogenesis and possibly the pathogenesis of azoospermia. We reconstructed all seminiferous tubules in 3D in musk shrew testes and found that a single, highly branched tubule dominates the testis. Spermatogenesis begins unusually early, and by 8 weeks, a mosaic pattern of active and inactive regions emerges, representing features that are distinct from those in mice and rats.